Electrochemical, spectroelectrochemical, and electrocatalytic properties of novel soluble phthalocyanines containing peripheral thymoxy and chloride units - ODABAŞ, ZAFER; ÖZKAYA, ALİ RIZA (My University, 2023)
© 2022 Elsevier B.V.Novel CoPc, CuPc, Fe(OAc)Pc and Mn(Cl)Pc were synthesized by using original 4-chloro-5-(2-isopropyl-5-methylphenoxy)phthalonitrile in order to investigate their potential redox applications suitable with their chemical and physical characteristics. The molecular structures of new compounds were determined with spectroscopic methods such as elemental analysis, FT-IR, UV–vis, NMR and MALDI TOF MS. Redox behaviours of Fe(OAc)Pc and Mn(Cl)Pc complexes have been probed by using diverse voltammetric techniques such as cyclic (CV) and square wave voltammetry (SWV). In addition, the colour alterations accompanying spectral changes were perused concurrently with electrocolorimetric measurements, and electrocatalytic efficiencies of the all compounds were perused in oxygen reduction reaction.
Keywords: Kimya; Fizikokimya; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Fiziksel ve Teorik Kimya; Fizik Bilimleri; İnorganik kimya; Malzeme Kimyası; Physical and Theoretical Chemistry; Physical Sciences; Materials Chemistry; Electrocatalitic activity; Electrochemistry; Phthalocyanines; Synthesis; Thymoxy; İn-situ Spectroelectrochemistry